PENGARUH PEMBERDAYAAN DAN MOTIVASI TERHADAP KOMITMEN ORGANISASIONAL DENGAN MEDIASI KEPUASAN KERJA (STUDI PADA PENYULUH BADAN PELAKSANA PENYULUHAN KABUPATEN TEMANGGUNG) (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study examined effect of empowerement and motivation to organizational commitment by mediation of job satisfaction on Badan Pelaksana Penyuluhan Kabupaten Temanggung. This study is aimed to identificate : a). positive effect of empowerement and job satisfaction, b). positive effect of motivation and job satisfaction, c). positive effect of empowerement and organizational commitment. d). positive effect motivation and organizational commitment, e). positive job satisfaction and organizational commitment.The object of polulation are Penyuluh PNS of Badan Pelaksana Penyuluhan Kabupaten Temanggung, 86 respondent. Collecting data using sensus methodes. Sample of this study covered from 85 respondens. The instrument is tested by validity test, factor analysis and reliability test (alpha cronbach) and linier regression. T test used to prove the hipotheses while effect mediation test to prove job satisfaction as mediation variabel. The study shows that emporement have positive effect and significant to job satisfaction; empowerement and job satisfaction have positive effect and significant to organizational commitment. This study indicated effect empowerement and organizational commitment was not mediated by job satisfaction. Key word : Empowerement, motivation, job satisfaction, and organizational commitment